Sex and aggression in f. Scott fitzgerrald's novel The great gatsby (1925): a psychoanalytic criticism - Wijayanti, Ana, Dr. M. Thoyibi, M.S, Titis Setyabudi, S.S. M. Hum (2014)
The major issue of this study is what and how causes of sex and aggression reflected in The Great Gatsby novel (1925) by F. Scott Fitzgerrald?. The objective of this study is, 1) to describe The Great Gatsby novel based on structural elements of novel, and 2) to analyze sex and aggression in The Great Gatsby novel(1925 by F. Scott Fitzgerrald based on a Psychoanalytic Criticism. The research is qualitative study. The researcher uses primary data source and secondary data source. The primary data sources The Great Gatsby novel by F. Scott Fitzgerrald and the secondary data sources related the study, such as: website, dictionary, some books that support the analysis. The data collection method used by the researcher is reading the novel, taking notes, arranging the data, selecting particular parts of the script, determining the character that will be analyzed, classifying and determining the relevant data and browsing on internet. The data analysis method is descriptive qualitative analysis descriptive analysis concerns with structural element of the novel on sex and aggression. The results of the study shows the following conclusions. First, based on the structural analysis, it can be concluded that there are several moral messages appear in The Great Gatsby novel, the author conveys a moral messages that this novel involve the love and lust sometimes cannot be distinguished from one another. Second based on psychoanalytic analysis it can be found that in this novel the author illustatees the psychological phenomenon related with causes of sex and aggression.